PERAN PEREMPUAN DALAM JARINGAN TERORISME ISIS DI INDONESIA - Nesa Wilda Musfia; Tri Cahyo Utomo; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2017)
Women’s role in terrorist groups has been widely discussed by scholars (Agara, 2015; Yasefi, 2014; Martin. 2014; Nurhayati, 2015; Ratri, 2011; Magrfur & muniroh, 2013). Especially, in the emergence of ISIS which increases a long list of women’s role in terror cases. This study aims to explain women’s role in ISIS terrorism networks in Indonesia and the reasons that triggered the women to be involved. This research was done by using qualitative research method with descriptive research type. This research was analyzed by using social identity theory, psychological terrorism theory, and “wani ing tata” concept as a cultural philosophy of Javanese culture. These theories were used in this research as theoretical frameworks. The result of this study shows that the roles that women have in the terrorist group were as important as those of men’s. ISIS has a different strategy in involving women compared to other terrorist groups. In ISIS, women are motivated to involve by individual psychology/psychological condition, their closest relatives, as well as personal experiences along with their social identity as muslims.